Influence of agroclimatic factors on the efficiency of multi-ovulation in cattle in the Peruvian tropics - Segura Portocarrero, Gleni Tatiana; Murga Valderrama, Nilton Luis; Lopez Lapa, Rainer Marco; Saucedo Uriarte, José Américo; Gongora Bardales, Deiner Jhonel; Frias Torres, Hugo; Poclín Rojas, Annie Yoselin; Depaz Hizo, Benjamin; Vasquez Tarrillo, Ronald Will; Heredia Vilchez, Lizeth Amparo; Ampuero Trigoso, Gustavo (Frontiers Media S.A., 2025)
Introduction: Agroclimatic conditions are key determinants in the development of animal production and reproduction, with specific breed differences in vulnerability to environmental stress. This research aims to determine the influence of agroclimatic factors on the efficiency of multi-ovulation in cattle in the Peruvian tropics.